JP2000297301A - Silicon carbide-based composite material, powder thereof, and production method thereof - Google Patents

Silicon carbide-based composite material, powder thereof, and production method thereof

Info

Publication number
JP2000297301A
JP2000297301A JP11107395A JP10739599A JP2000297301A JP 2000297301 A JP2000297301 A JP 2000297301A JP 11107395 A JP11107395 A JP 11107395A JP 10739599 A JP10739599 A JP 10739599A JP 2000297301 A JP2000297301 A JP 2000297301A
Authority
JP
Japan
Prior art keywords
silicon carbide
powder
component
composite material
based composite
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Pending
Application number
JP11107395A
Other languages
Japanese (ja)
Inventor
Chihiro Kawai
千尋 河合
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Sumitomo Electric Industries Ltd
Original Assignee
Sumitomo Electric Industries Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Sumitomo Electric Industries Ltd filed Critical Sumitomo Electric Industries Ltd
Priority to JP11107395A priority Critical patent/JP2000297301A/en
Publication of JP2000297301A publication Critical patent/JP2000297301A/en
Pending legal-status Critical Current

Links

Classifications

    • C—CHEMISTRY; METALLURGY
    • C22—METALLURGY; FERROUS OR NON-FERROUS ALLOYS; TREATMENT OF ALLOYS OR NON-FERROUS METALS
    • C22C—ALLOYS
    • C22C32/00—Non-ferrous alloys containing at least 5% by weight but less than 50% by weight of oxides, carbides, borides, nitrides, silicides or other metal compounds, e.g. oxynitrides, sulfides, whether added as such or formed in situ
    • C22C32/0047—Non-ferrous alloys containing at least 5% by weight but less than 50% by weight of oxides, carbides, borides, nitrides, silicides or other metal compounds, e.g. oxynitrides, sulfides, whether added as such or formed in situ with carbides, nitrides, borides or silicides as the main non-metallic constituents
    • C22C32/0052—Non-ferrous alloys containing at least 5% by weight but less than 50% by weight of oxides, carbides, borides, nitrides, silicides or other metal compounds, e.g. oxynitrides, sulfides, whether added as such or formed in situ with carbides, nitrides, borides or silicides as the main non-metallic constituents only carbides
    • C22C32/0063—Non-ferrous alloys containing at least 5% by weight but less than 50% by weight of oxides, carbides, borides, nitrides, silicides or other metal compounds, e.g. oxynitrides, sulfides, whether added as such or formed in situ with carbides, nitrides, borides or silicides as the main non-metallic constituents only carbides based on SiC

Landscapes

  • Powder Metallurgy (AREA)
  • Cooling Or The Like Of Semiconductors Or Solid State Devices (AREA)

Abstract

(57)【要約】 【課題】 放熱基板、特に半導体装置に有用な高い熱伝
導率のAl−SiC系の炭化珪素系複合材料を提供す
る。 【解決手段】 アルミニウムを主成分とする金属を第一
成分とし、炭化珪素を主成分とする粒子を第二成分とす
る炭化珪素系複合材料の粉末であって、その平均粒径は
5〜100μmであり、その個々の粒子は、平均粒径5
μm以下の第二成分の粒子表面を第一成分の複数の粒子
が覆っており、該粉末全体の炭化珪素の量が10〜85
重量%である炭化珪素系複合材料の粉末である。またこ
の粉末を用いて得られる相対密度が90%以上、熱伝導
率が220W/m・K以上の炭化珪素系複合材料であ
る。この粉末は、第一・第二両成分粉末をメカニカルア
ロイングすることによって得られる。
PROBLEM TO BE SOLVED: To provide an Al-SiC-based silicon carbide composite material having a high thermal conductivity, which is useful for a heat dissipation substrate, particularly for a semiconductor device. SOLUTION: This is a powder of a silicon carbide-based composite material containing a metal mainly composed of aluminum as a first component and particles mainly composed of silicon carbide as a second component, and has an average particle diameter of 5 to 100 μm. And the individual particles have an average particle size of 5
A plurality of particles of the first component cover the particle surface of the second component having a particle size of μm or less, and the amount of silicon carbide in the entire powder is 10 to 85.
It is a powder of a silicon carbide-based composite material in weight%. A silicon carbide-based composite material having a relative density of 90% or more and a thermal conductivity of 220 W / m · K or more obtained using this powder. This powder is obtained by mechanically alloying the first and second component powders.

Description

【発明の詳細な説明】DETAILED DESCRIPTION OF THE INVENTION

【0001】[0001]

【発明の属する技術分野】本発明は、各種装置・機器に
用いられる放熱基板、特に半導体装置の放熱基板に用い
られる高い熱伝導性を有する炭化珪素系複合材料に関
し、特にそれを製造するための粉末、同粉末から得られ
る炭化珪素系複合材料ならびに同材料を用いた半導体装
置に関する。
BACKGROUND OF THE INVENTION 1. Field of the Invention The present invention relates to a heat dissipating substrate used for various devices and equipment, and more particularly to a silicon carbide composite material having high thermal conductivity used for a heat dissipating substrate of a semiconductor device. The present invention relates to a powder, a silicon carbide-based composite material obtained from the powder, and a semiconductor device using the same.

【0002】[0002]

【従来の技術】近年半導体装置の高速演算・高集積化に
対する市場の要求は急速に高まりつつある。それととも
に、同装置の半導体素子搭載用放熱基板には、同素子か
ら発生する熱をより一層効率良く逃がすため、その熱伝
導率のより一層の向上が求められてきた。さらに同素子
ならびに同基板に隣接配置された同装置内の他の部材
(周辺部材)との間の熱歪みをより一層小さくするため
に、より一層それらに近い熱膨張係数を有するものであ
ることも求められてきた。 具体的には、半導体素子と
して通常用いられるSi、GaAsの熱膨張係数がそれ
ぞれ4.2×10-6/℃、6.5×10-6/℃であり、
半導体装置の外囲器材として通常用いられるアルミナセ
ラミックスのそれが6.5×10-6/℃程度であること
から、同基板の熱膨張係数はこれらの値に近いことが望
まれる。
2. Description of the Related Art In recent years, market demands for high-speed operation and high integration of semiconductor devices have been rapidly increasing. At the same time, the heat radiation board for mounting the semiconductor element of the device has been required to further improve the thermal conductivity in order to more efficiently release the heat generated from the element. Furthermore, other elements in the same device and the same device arranged adjacent to the same substrate
In order to further reduce the thermal strain between them and the (peripheral member), it is also required to have a thermal expansion coefficient closer to them. Specifically, Si usually used as the semiconductor element, the thermal expansion coefficient of GaAs are each 4.2 × 10 -6 /℃,6.5×10 -6 / ℃ ,
Since that of alumina ceramics usually used as an envelope of a semiconductor device is about 6.5 × 10 −6 / ° C., it is desired that the thermal expansion coefficient of the substrate be close to these values.

【0003】また近年のエレクトロニクス機器の応用範
囲の著しい拡張にともない、半導体装置の使用範囲はよ
り一層多様化しつつある。その中で、高出力の交流変換
機器・周波数変換機器等のいわゆる半導体パワーデバイ
ス機器への利用が増えつつある。これらのデバイスで
は、半導体素子からの発熱が半導体メモリーやマイクロ
プロセッサーに比べ数倍から数十倍(通常例えば数十W)
にも及ぶ。このためこれらの機器に使われる放熱基板
は、その熱伝導率を格段に向上させるとともに、その熱
膨張係数の周辺部材のそれとの整合性を高めることが重
要である。したがってその基本構造も、通常は例えば以
下のようになっている。まずSi半導体素子を第一の放
熱基板である高熱伝導性の窒化アルミニウム(以下単に
AlNとも言う)セラミック基板上に載せる。次いでそ
の第一の放熱基板の下に銅等のより高熱伝導性の金属か
らなる第二の放熱基板を配置する。さらにこの第二の基
板の下に、これを水冷または空冷可能な放熱機構を配置
する。以上のような構造によって外部に遅滞なく熱を逃
がす。したがって複雑な放熱構造とならざるを得ない。
この構造においては、第一の放熱基板であるAlNセラ
ミックスに170W/m・K程度のものを用いるとする
と、第二の放熱基板は、この第一の基板から伝達された
熱をその下の放熱機構に遅滞なく逃がす必要がある。こ
のため第二の基板としては、室温で少なくとも200W
/m・K以上の高い熱伝導率と第一の基板との熱膨張係
数の整合のため、10×10-6/℃以下、特に8×10
-6/℃以下の低い熱膨張係数を有するものが要求され
る。
[0003] Further, with the remarkable expansion of the application range of electronic equipment in recent years, the use range of semiconductor devices has been further diversified. Among them, applications to so-called semiconductor power device devices such as high-output AC converters and frequency converters are increasing. In these devices, the heat generated by the semiconductor elements is several times to several tens times (typically, for example, several tens of watts) compared to semiconductor memories and microprocessors.
Extend to For this reason, it is important for the heat radiation board used in these devices to remarkably improve the thermal conductivity and to improve the matching of the thermal expansion coefficient with that of the peripheral members. Therefore, the basic structure is usually as follows, for example. First, a Si semiconductor element is mounted on a high thermal conductive aluminum nitride (hereinafter, also simply referred to as AlN) ceramic substrate which is a first heat dissipation substrate. Next, a second heat radiating substrate made of a metal having higher thermal conductivity such as copper is arranged under the first heat radiating substrate. Further, a heat dissipating mechanism capable of water cooling or air cooling is disposed below the second substrate. The above structure allows heat to escape to the outside without delay. Therefore, a complicated heat dissipation structure is inevitable.
In this structure, assuming that AlN ceramics of about 170 W / m · K is used as the first heat radiation substrate, the second heat radiation substrate transfers the heat transmitted from the first substrate to the heat radiation thereunder. It is necessary to escape to the mechanism without delay. For this reason, the second substrate should be at least 200 W at room temperature.
/ M · K or more and 10 × 10 −6 / ° C. or less, especially 8 × 10
A material having a low thermal expansion coefficient of -6 / ° C or less is required.

【0004】特にパワーデバイスの内でも実用時の発熱
量の大きなものでは、放熱基板自体の温度も100℃以
上に昇温することがあるため、このような温度での高い
熱伝導率を要求される場合もある。したがって、このよ
うな温度下でも150W/m・K以上の熱伝導率のもの
が要求される。またその容量が大きくなればなるほどS
i半導体素子のサイズも大きくなる。それ故それを搭載
する放熱基板も大きくせざるを得ない。例えばパソコン
用の基板が高々20〜40mm角程度のであるのに対
し、容量の大きなパワーデバイスでは、200mm角を
越えるものも求められつつある。このような大きな基板
では、実装時のその寸法精度のみならず高温でそれの低
下しないことが要求されている。すなわち高温で基板に
反りや変形が生じると、上記した基板の下に配置される
放熱機構(ラジエターやフィン等)との界面に隙間ができ
放熱効率が落ちる。また最悪の場合半導体素子が破壊す
る場合もある。それ故高温での放熱基板の優れた熱伝導
性の確保は、重要な課題である。
[0004] In particular, among power devices having a large heat value in practical use, the temperature of the heat radiation substrate itself may rise to 100 ° C or more, so that a high thermal conductivity at such a temperature is required. In some cases. Therefore, a material having a thermal conductivity of 150 W / m · K or more is required even at such a temperature. Also, the larger the capacity, the more S
The size of the i semiconductor element also increases. Therefore, the heat dissipating substrate on which it is mounted must be enlarged. For example, a substrate for a personal computer has a size of at most about 20 to 40 mm square, while a power device having a large capacity is required to have a size exceeding 200 mm square. In such a large substrate, not only its dimensional accuracy at the time of mounting but also its lowering at a high temperature is required. That is, when the substrate is warped or deformed at a high temperature, a gap is formed at an interface with a heat radiation mechanism (such as a radiator or a fin) disposed below the substrate, thereby lowering the heat radiation efficiency. In the worst case, the semiconductor element may be destroyed. Therefore, ensuring excellent thermal conductivity of the heat dissipation board at high temperatures is an important issue.

【0005】またこのような基板には、従来より例えば
Cu−W系やCu−Mo系の複合合金からなるものが用
いられてきた。これらの基板は、原料が高価なためにコ
スト高になるとともに重量が大きくなるという問題があ
った。そこで、最近は安価で軽量な材料として各種のア
ルミニウム(以下単にAlとも言う)複合合金が注目され
るようになってきた。中でもAlと炭化珪素(以下単に
SiCとも言う)を主成分とするAl−SiC系複合合
金は、それらの原料が比較的安価であり、軽量かつ高熱
伝導性である。なお通常市販されている純粋なAl、S
iC単体の密度は、それぞれ2.7g/cm3程度、
3.2g/cm3程度、熱伝導率は、それぞれ240W
/m・K程度、200〜300W/m・K程度までであ
るが、さらにその純度や欠陥濃度を調整すれば、その熱
伝導率のレベルはさらに向上するものと思われる。その
ため、特に注目されている材料である。また純粋なSi
C単体、Al単体の熱膨張係数はそれぞれ4.2×10
-6/℃程度、24×10-6/℃程度であり、それらを複
合化することによって、その熱膨張係数が広い範囲で制
御可能となる。したがってこの点でも有利である。
For such a substrate, a substrate made of, for example, a Cu-W or Cu-Mo composite alloy has been used. These substrates have a problem that the cost is high and the weight is large because the raw material is expensive. Therefore, recently, various aluminum (hereinafter, also simply referred to as Al) composite alloys have been attracting attention as inexpensive and lightweight materials. Above all, Al-SiC-based composite alloys containing Al and silicon carbide (hereinafter also simply referred to as SiC) as main components are relatively inexpensive, lightweight, and have high thermal conductivity. In addition, pure Al, S which is usually commercially available
The density of iC alone is about 2.7 g / cm 3 ,
3.2 g / cm 3 , thermal conductivity 240 W
/ M · K, up to about 200 to 300 W / m · K, but it is expected that the level of thermal conductivity will be further improved by further adjusting its purity and defect concentration. Therefore, it is a material that has received special attention. Also pure Si
The thermal expansion coefficients of C alone and Al alone are 4.2 × 10
-6 / ° C. and 24 × 10 -6 / ° C., and by combining them, the thermal expansion coefficient can be controlled in a wide range. Therefore, this point is also advantageous.

【0006】かかるAl−SiC系複合合金およびその
製造方法については、(1)特開平1−501489号公
報、(2)特開平2−343729号公報、(3)特開昭6
1−222668号公報および(4)特開平9−1577
73号公報に開示されている。(1)は、SiCとAlの
混合物中のAlを溶融させて鋳造法によって固化する方
法に関するものである。 (2)、(3)は、いずれもSi
C多孔体の空隙にAlを溶浸する方法に関するものであ
る。この内(3)は、加圧下でAlを溶浸する、いわゆる
加圧溶浸法に関するものである。また(4)は、SiCと
Alの混合粉末の成形体かまたはそれをホットプレスし
たものを型内に配置し、これを真空中、Alの融点以上
の温度で液相焼結する方法に関するものである。
The Al-SiC-based composite alloy and the method for producing the same are described in (1) JP-A-1-501489, (2) JP-A-2-343729, and (3) JP-A-6
1-222668 and (4) JP-A-9-1577.
No. 73 is disclosed. (1) relates to a method in which Al in a mixture of SiC and Al is melted and solidified by a casting method. (2) and (3) are both Si
The present invention relates to a method of infiltrating Al into voids of a C porous body. (3) relates to a so-called pressure infiltration method in which Al is infiltrated under pressure. Further, (4) relates to a method of sintering a compact of a mixed powder of SiC and Al or a hot-pressed compact thereof in a mold and subjecting the compact to a liquid phase sintering at a temperature equal to or higher than the melting point of Al in a vacuum. It is.

【0007】本発明者等は、特願平9−136164号
にて、(5)液相焼結法によって得られ、その熱伝導率が
180W/m・K以上のアルミニウム−炭化珪素系複合
材料を提示している。この複合材料は、例えば10〜7
0重量%の粒子状SiC粉末とAl粉末との混合粉末を
成形した後、99%以上の窒素を含み、酸素濃度が20
0ppm以下、露点が−20℃以下の非酸化性雰囲気
中、600〜750℃で焼結する工程によって得られ
る。 また本発明者等は、特願平9−93467号に
て、(6)その熱膨張係数が18×10-6/℃以下、その
熱伝導率が230W/m・K以上であり、焼結後の寸法
が実用寸法に近い、いわゆるネットシェイプなアルミニ
ウム−炭化珪素系複合材料も提示している。さらに本発
明者等は、特願平10−41447号にて、(7)常圧焼
結法とHIP法とを組み合わせた同複合材料の製造方法
を提案している。それによれば、例えば粒子状SiCを
10〜70重量%混合したAl−SiC系混合粉末の成
形体を、窒素ガスを99%以上含む非酸化性雰囲気中、
600℃以上、Alの溶融温度以下の温度範囲で常圧焼
結し、その後金属容器に封入して700℃以上の温度で
HIPすることによって、均質でその熱伝導率が200
W/m・K以上のアルミニウム−炭化珪素系複合材料が
得られている。
The present inventors have disclosed in Japanese Patent Application No. Hei 9-136164 (5) an aluminum-silicon carbide composite material obtained by (5) a liquid phase sintering method and having a thermal conductivity of 180 W / m · K or more. Is presented. This composite material is, for example, 10-7
After molding a mixed powder of 0% by weight of particulate SiC powder and Al powder, it contains 99% or more of nitrogen and has an oxygen concentration of 20% or more.
It is obtained by a step of sintering at 600 to 750 ° C in a non-oxidizing atmosphere having 0 ppm or less and a dew point of -20 ° C or less. Further, the present inventors have disclosed in Japanese Patent Application No. 9-93467 that (6) its thermal expansion coefficient is 18 × 10 −6 / ° C. or less, its thermal conductivity is 230 W / m · K or more, A so-called net-shaped aluminum-silicon carbide composite material whose subsequent dimensions are close to practical dimensions is also proposed. Further, the present inventors have proposed in Japanese Patent Application No. 10-41447 a method (7) for producing the same composite material by combining the normal pressure sintering method and the HIP method. According to this, for example, a compact of an Al—SiC-based mixed powder in which 10 to 70% by weight of particulate SiC is mixed is placed in a non-oxidizing atmosphere containing 99% or more of nitrogen gas.
By normal pressure sintering in the temperature range of 600 ° C. or more and Al melting temperature or less, and then sealed in a metal container and HIPed at a temperature of 700 ° C. or more, it is homogeneous and has a thermal conductivity of 200 ° C.
An aluminum-silicon carbide based composite material of W / m · K or more has been obtained.

【0008】さらに(8)特開平9−157773号公報
には、Al粉末とSiC粉末との混合物をホットプレス
し、成形と焼結とを同時に行う方法が開示されている。
その方法は、Al10〜80体積%、残部SiCの混合
粉末を成形し、Alの溶融点以上の温度下500kg/
cm2以上の圧力でホットプレスするものである。この
方法によって150〜280W/m・Kの熱伝導率のア
ルミニウム−炭化珪素系複合材料が得られている。
Further, (8) Japanese Patent Application Laid-Open No. 9-157773 discloses a method in which a mixture of an Al powder and a SiC powder is hot pressed to simultaneously perform molding and sintering.
The method is to form a mixed powder of 10 to 80% by volume of Al and the balance of SiC, and 500 kg /
Hot pressing is performed at a pressure of 2 cm 2 or more. According to this method, an aluminum-silicon carbide composite material having a thermal conductivity of 150 to 280 W / m · K is obtained.

【0009】[0009]

【発明が解決しようとする課題】以上述べたような複合
材料を大きな放熱量を要求される基板、特に半導体パワ
ーデバイス用の基板のように実用サイズが比較的大きく
放熱量の多い放熱基板として使用するためには、以下に
述べる解決すべきいくつかの課題が残っている。例えば
上記(1)に記載のAl−SiC系複合材料の製造方法で
は、Al溶湯を鋳型に流し込み、SiC粒子を分散させ
て固化する鋳造法を用いる。したがってAlとSiCの
密度差により冷却時に成形体中のSiC粒子の偏析が生
じ、固化体の組成が不均一になり易い。このため固化体
の表面がAlまたはAl合金からなる被覆層(以下この
層をAl被覆層とも言う)により覆われるのは避けられ
ない。通常この被覆層の厚みは、固化体の表面の部所に
よってかなりばらつく。さらにこの被覆層からなる固化
体の表面部とその内部との間では熱膨張係数にかなり差
があるため、両者の界面に熱が伝わるとそこに熱応力が
生じることになる。 それ故この被覆層を残してこの素
材を半導体素子搭載用の放熱基板に用いると、発生した
熱応力によって基板に反りや変形が生じ、その結果半導
体素子や周辺部材と基板との間に亀裂が生じたり、半導
体素子や周辺部材が変形したり、破壊したりする。した
がって、この被覆層は予め完全に除去する必要がある。
しかもこの除去は、上記のように被覆層の厚みにばらつ
きがあるため、軟質延性のAlを主成分とする相と剛性
の高いSiCを含む相とが共存する部分の加工となる。
したがって難加工となる。
The composite material described above is used as a substrate requiring a large amount of heat radiation, particularly a heat radiation substrate having a relatively large practical size and a large amount of heat radiation, such as a substrate for a semiconductor power device. In order to do so, there remain some issues to be solved as described below. For example, in the method for producing an Al-SiC-based composite material described in the above (1), a casting method in which an Al melt is poured into a mold, and the SiC particles are dispersed and solidified. Therefore, the density difference between Al and SiC causes segregation of SiC particles in the compact during cooling, and the composition of the solidified body tends to be non-uniform. Therefore, it is inevitable that the surface of the solidified body is covered with a coating layer made of Al or an Al alloy (hereinafter, this layer is also referred to as an Al coating layer). Usually, the thickness of the coating layer varies considerably depending on the location on the surface of the solidified body. Further, since there is a considerable difference in the thermal expansion coefficient between the surface portion of the solidified body made of the coating layer and the inside thereof, when heat is transmitted to the interface between them, thermal stress is generated there. Therefore, if this material is used as a heat dissipation board for mounting semiconductor devices while leaving this coating layer, the substrate will be warped or deformed by the generated thermal stress, and as a result, cracks will occur between the semiconductor device and peripheral members and the substrate. Or a semiconductor element or a peripheral member is deformed or broken. Therefore, it is necessary to completely remove this coating layer in advance.
In addition, since the thickness of the coating layer varies as described above, the removal is processing of a portion where a soft ductile Al-based phase and a highly rigid SiC-based phase coexist.
Therefore, it becomes difficult to process.

【0010】上記(2)および(3)のAl−SiC系複合
材料の製造方法では、AlがSiC多孔体の空隙に溶浸
される。この場合鉄鋼の鋳造時に発生するような溶融A
lの引け巣を防ぎ、またSiCの空隙内にAlを完全に
充填して緻密な複合合金を得る必要がある。このため通
常SiC多孔体の外周に過剰なAlが溶浸剤として配置
される。溶浸後この過剰なAlが溶浸体の外周に溶出固
着し、その除去に多大の手間がかかる。また予めAlと
SiCを主成分とする混合粉末を成形し、焼結する上記
(5)に記載された方法でもAlの融点を越える温度で焼
結すると、軽度ではあるがこれと同じ現象が生じる。
In the above-mentioned methods (2) and (3) for producing an Al—SiC composite material, Al is infiltrated into the voids of the porous SiC material. In this case, the melting A which is generated during the casting of steel
It is necessary to obtain a dense composite alloy by preventing shrinkage cavities of 1 and completely filling Al in the voids of SiC. For this reason, usually excess Al is disposed as an infiltrant on the outer periphery of the porous SiC body. After the infiltration, the excess Al is eluted and fixed on the outer periphery of the infiltrated body, and it takes a lot of trouble to remove it. In addition, a mixed powder containing Al and SiC as main components is previously molded and sintered.
In the method described in (5), when the sintering is performed at a temperature exceeding the melting point of Al, the same phenomenon occurs, albeit mildly.

【0011】そこでこのような外周へのAlの溶出固着
を防止するために、上記(6)に記載されたように、Al
を溶浸する前にSiC多孔体の外周にその溶出防止剤と
同溶浸を促す溶浸促進剤との混合物からなる薄い層を塗
布・形成することも一策ではある。しかしながらこれら
の層の塗布および溶浸後の除去には手間がかかる。
Therefore, in order to prevent such elution and fixation of Al on the outer periphery, as described in (6) above,
Before infiltration, a thin layer made of a mixture of the anti-elution agent and an infiltration accelerator that promotes the infiltration is also applied and formed on the outer periphery of the porous SiC body. However, applying these layers and removing them after infiltration is troublesome.

【0012】また上記(3)の加圧溶浸法では、一軸加圧
可能な型内にSiC多孔体を配置し、その上部にAlま
たはAl合金を置いて、真空中でAlを溶融させつつこ
れを外部から一軸加圧してSiC多孔体内に強制的に充
填する工程を踏む。この場合最終的に溶浸体は温度勾配
をつけて下部から徐々に冷却する。この時溶浸体内部の
SiC骨格部とAlによって充填された部分の熱膨張係
数の差が大きいために、冷却時にAlが溶浸体内に引け
てAlが未溶浸の部分(上述の引け巣に相当する)ができ
易い。したがって、冷却時の温度勾配と加圧・加熱のプ
ログラムとを同時に精度良く制御できる複雑な制御機構
が必要になる。したがってその装置はかなり高価なもの
となる。
In the pressure infiltration method (3), a porous SiC body is placed in a mold that can be uniaxially pressed, and Al or an Al alloy is placed on top of the porous body. The step of uniaxially applying the pressure from the outside and forcibly filling the SiC porous body is performed. In this case, finally, the infiltrated body is gradually cooled from the lower part with a temperature gradient. At this time, since the difference in thermal expansion coefficient between the SiC skeleton portion inside the infiltration body and the portion filled with Al is large, Al is pulled into the infiltration body during cooling and Al is not infiltrated (the above-mentioned shrinkage cavity). (Equivalent to). Therefore, a complicated control mechanism that can simultaneously and accurately control the temperature gradient at the time of cooling and the program of pressurization and heating is required. The device is therefore quite expensive.

【0013】さらに上記(4)に記載された型内ホットプ
レスによる方法では、以下に述べるような生産上・品質
上の問題がある。例えばホットプレス装置に連続式のも
のを用いると、真空雰囲気にするとともにその温度をA
lの溶融点以上に上げるため、型の外への溶融物の流出
を抑える必要がある。したがって成分量のばらつきを抑
え目的とする均一組成のものを得ようとすると、非常に
高価な製造装置が必要となる。一方同装置をバッチ式に
する場合には、溶融物の型外への流出は、連続式のもの
に比べいくぶん抑えることはできる。しかしその一方で
成形体の型への装填、所定の温度プログラムでの保持と
冷却の一連の工程を断続的に繰り返すことになるため、
この方式は生産性に欠ける。
Further, the method using hot pressing in a mold described in the above (4) has problems in production and quality as described below. For example, if a continuous type hot press device is used, a vacuum atmosphere and a temperature of A
In order to increase the melting point to 1 or more, it is necessary to suppress the outflow of the melt out of the mold. Therefore, in order to suppress the variation of the component amount and obtain a target having a uniform composition, an extremely expensive manufacturing apparatus is required. On the other hand, when the apparatus is of a batch type, the outflow of the melt out of the mold can be somewhat suppressed as compared with the continuous type. However, on the other hand, a series of steps of loading the molded body into the mold, holding and cooling at a predetermined temperature program are intermittently repeated,
This method lacks productivity.

【0014】以上詳述したように、従来のAl−SiC
系の複合材料の製造には品質上・生産上のいくつかの課
題をかかえている。したがってAl−SiC系の複合材
料は、特に半導体パワーモジュールのような高い放熱性
を要求される基板の一つとして、その性能面で最近有望
視されているにもかかわらず、従来から行われてきた鋳
造法、溶浸法、焼結法、ホットプレス法やそれらを組み
合わせたいずれの方法でも満足のゆく本来の性能レベル
のものは得られていない。その理由の一つとして以下の
ことが考えられる。すなわちAlとSiCの間の濡れ性
を改善してAl融液のSiC粒子間への自発的な浸透を
促したり、空孔の発生を抑えるためにAl中にSi等の
従成分を添加したり、またはこれらの従成分を不純物と
して含むAlを用いたりする場合が多々あった。このた
めこれらの従成分の介在によって複合材料の熱伝導率の
低下は避けられなかった。したがって優れた熱伝導性を
確保するためには、できる限り純粋なAl粉末を用いつ
つ、それとSiC粒子表面との濡れ性をいかに確保する
かが重要な課題である。
As described in detail above, the conventional Al-SiC
There are some quality and production issues in the production of composite materials. Therefore, an Al-SiC-based composite material has been used as one of the substrates requiring high heat dissipation, such as a semiconductor power module, despite its recent promising performance. Any satisfactory casting method, infiltration method, sintering method, hot pressing method or any combination of these methods has not been able to obtain a satisfactory original performance level. The following can be considered as one of the reasons. That is, the wettability between Al and SiC is improved to promote spontaneous infiltration of the Al melt between the SiC particles, or a minor component such as Si is added to Al to suppress generation of voids. Or Al containing these minor components as impurities in many cases. For this reason, a decrease in the thermal conductivity of the composite material was unavoidable due to the interposition of these auxiliary components. Therefore, in order to ensure excellent thermal conductivity, it is important to use pure Al powder as much as possible and to ensure the wettability between the powder and the surface of the SiC particles.

【0015】一般に物質の熱伝導率は、以下の式に示さ
れるように物質の密度、比熱、熱拡散率の関数である。 熱伝導率=密度×比熱×熱拡散率 式(1) ここで複合材料の場合、比熱はその成分組成比率によっ
て決まる。したがって、組成が同じであれば、その熱伝
導率向上のためにはその密度と熱拡散率を上げることが
必要である。上記した従来のAl−SiC系の複合材料
では、その密度が99%以上のものでもその熱伝導率が
200W/m・K程度あり、熱伝導率向上のためには、
特に熱拡散率を向上させる必要がある。
In general, the thermal conductivity of a substance is a function of the density, specific heat, and thermal diffusivity of the substance as shown in the following equation. Thermal conductivity = Density x Specific heat x Thermal diffusivity Formula (1) Here, in the case of a composite material, the specific heat is determined by the composition ratio of the components. Therefore, if the composition is the same, it is necessary to increase the density and the thermal diffusivity in order to improve the thermal conductivity. In the above-mentioned conventional Al-SiC-based composite material, even if its density is 99% or more, its thermal conductivity is about 200 W / m · K.
In particular, it is necessary to improve the thermal diffusivity.

【0016】Al−SiC系の複合材料では、その熱拡
散率はAlとSiCのそれぞれの熱拡散率および両相界
面の密着状態によって決まるものと考えられる。両相界
面の密着の程度は、基本的に密度が高ければ高いほど向
上する。それ故Al−SiC系の複合材料の熱拡散率を
向上させる一つの方向として、両成分の純度を保ちつつ
両者の確実な濡れ性の確保が重要となる。
It is considered that the thermal diffusivity of the Al-SiC-based composite material is determined by the thermal diffusivity of Al and SiC and the state of adhesion between the two phases. The degree of adhesion at the interface between the two phases basically improves as the density increases. Therefore, as one direction to improve the thermal diffusivity of the Al-SiC-based composite material, it is important to ensure the wettability of both components while maintaining the purity of both components.

【0017】本発明者等は、上記した従来の課題を解決
するために、特にSiC量の多い組成域での熱伝導性の
向上を重点に置いて研究を重ねてきた。その結果、既に
特願平10−260003号にて、SiC粒子の欠陥や
不純物の量を減らすことによって、この課題を克服でき
る見通しを得た。しかしながら、この方法ではその高い
熱伝導性を確保するため、比較的表面酸素量の少ないA
l粉末および純度の高いSiCの粉末を予め準備する必
要があり、その調製に手間がかかる。また両成分の純度
が高いため、特にAl粉末の表面が酸化され易い。それ
故焼成時の濡れ性を確保するためには、通常成形時に高
い圧力をかけて、その表面の酸化皮膜を破るとともに、
十分に両成分粒子を密着させる必要がある。したがって
SiC粉末による型の消耗が早くなる。したがってこの
方法では優れた熱伝導性の材料は得られるが、より生産
性の高い手段が求められる。
In order to solve the above-mentioned conventional problems, the present inventors have repeatedly studied with an emphasis on improving the thermal conductivity particularly in a composition region having a large amount of SiC. As a result, in Japanese Patent Application No. 10-260003, it has been expected that this problem can be overcome by reducing the amount of defects and impurities in SiC particles. However, in this method, in order to secure the high thermal conductivity, A having a relatively small amount of surface oxygen is used.
It is necessary to prepare 1 powder and high-purity SiC powder in advance, and the preparation thereof is troublesome. Further, since the purity of both components is high, the surface of the Al powder is particularly easily oxidized. Therefore, in order to ensure wettability during firing, high pressure is usually applied during molding to break the oxide film on the surface,
It is necessary to sufficiently adhere both component particles. Therefore, the mold is quickly consumed by the SiC powder. Therefore, this method can provide a material having excellent heat conductivity, but requires means with higher productivity.

【0018】一方表面酸素量の多い市販のAl粉末を用
いれば、原料コストは下がる。しかしその場合でもSi
C粉末との濡れ性を確保し、緻密に両者を複合化するた
めには予めその表面の酸化膜を破っておく必要がある。
このため上記の方法以上に高い圧力で成形する必要があ
り、型の消耗がやはり問題となる。そこで本発明者等
は、Alを主成分とする粉末成形体の脱酸素のため加熱
処理を追加し、比較的低い圧力で成形できる製造方法
を、特願平10−369300号にて提案した。しかし
この方法では、成形体内部の両成分間の濡れが不十分な
ため空孔が残り、本来の高い熱伝導率が得られないとい
う問題がある。
On the other hand, when a commercially available Al powder having a large surface oxygen content is used, the raw material cost is reduced. However, even in that case, Si
In order to ensure the wettability with the C powder and to precisely combine the two, it is necessary to break the oxide film on the surface in advance.
For this reason, it is necessary to mold at a higher pressure than the above method, and the consumption of the mold is still a problem. Therefore, the present inventors have proposed a manufacturing method in which a heat treatment is added for deoxidizing a powder compact mainly containing Al and compaction can be performed at a relatively low pressure in Japanese Patent Application No. 10-369300. However, this method has a problem that voids remain due to insufficient wetting between the two components inside the molded body, and the originally high thermal conductivity cannot be obtained.

【0019】なお前述の(7)および(8)に紹介され
ているように熱間で加圧焼結する方法であれば、緻密で
かなり高い熱伝導性の材料を得ることはできる。しかし
ながらこれらの方法は生産性に欠ける。したがってSi
C量が50重量%以上の組成域では、安価な常圧下の焼
成によって200W/m・Kを越える高い熱伝導率の材
料は未だに得られていない。
As described in the above (7) and (8), if the method is pressure sintering under hot pressure, it is possible to obtain a dense and highly heat-conductive material. However, these methods lack productivity. Therefore, Si
In the composition range where the C content is 50% by weight or more, a material having a high thermal conductivity exceeding 200 W / m · K has not yet been obtained by inexpensive firing under normal pressure.

【0020】[0020]

【課題を解決するための手段】したがって本発明の目的
は、以上述べた従来の炭化珪素系複合材料の品質上・生
産上の課題を克服し200W/m・Kを越える高い熱伝
導率の材料を、常圧下の焼成で安価に提供することであ
る。
SUMMARY OF THE INVENTION Accordingly, an object of the present invention is to overcome the above-mentioned problems in quality and production of the conventional silicon carbide composite material and to provide a material having a high thermal conductivity exceeding 200 W / m · K. Is provided at low cost by firing under normal pressure.

【0021】すなわち本発明で提供される炭化珪素系複
合材料の粉末は、アルミニウムを主成分とする金属を第
一成分とし、炭化珪素を主成分とする粒子を第二成分と
する粉末であって、その平均粒径は5〜100μmであ
り、その個々の粒子は、平均粒径5μm以下の第二成分
の粒子表面を第一成分の複数の粒子が覆っており、同粉
末全体の炭化珪素の量が10〜85重量%である。
That is, the powder of the silicon carbide-based composite material provided by the present invention is a powder containing a metal containing aluminum as a main component as a first component and particles containing silicon carbide as a main component as a second component. The average particle size is 5 to 100 μm, and the individual particles have a plurality of particles of the first component covering the particle surface of the second component having an average particle size of 5 μm or less. The amount is from 10 to 85% by weight.

【0022】また本発明の炭化珪素系複合材料は、上記
の粉末を用いて得られ、その相対密度が90%以上、室
温での熱伝導率が220W/m・K以上の材料である。
さらに本発明には、この炭化珪素系複合材料を用いた半
導体装置も含まれる。
The silicon carbide composite material of the present invention is a material obtained by using the above powder, having a relative density of 90% or more and a thermal conductivity at room temperature of 220 W / m · K or more.
The present invention also includes a semiconductor device using the silicon carbide composite material.

【0023】本発明の上記炭化珪素系複合材料の粉末
は、第一成分としてアルミニウムを主成分とする金属の
粉末15〜90重量%および第二成分として平均粒径が
10〜200μmの炭化珪素粉末10〜85重量%を準
備する工程1と、これらの粉末を非酸化性雰囲気中で第
二成分の平均粒径が5μm以下になるまでメカニカルア
ロイングする工程2とを含む方法で製造される。また本
発明の粉末の製造方法には、工程2のメカニカルアロイ
ングを10G以上の加速度で行う手段も含まれる。
The silicon carbide-based composite material powder according to the present invention is preferably a silicon carbide powder having an average particle diameter of 10 to 200 μm as a first component, and a metal powder containing aluminum as a main component as 15 to 90% by weight as a first component. It is manufactured by a method including a step 1 of preparing 10 to 85% by weight and a step 2 of mechanically alloying these powders in a non-oxidizing atmosphere until the average particle diameter of the second component becomes 5 μm or less. The method for producing a powder of the present invention also includes means for performing the mechanical alloying in Step 2 at an acceleration of 10 G or more.

【0024】本発明の炭化珪素系複合材料は、以上の手
順で得られた粉末を成形し成形体とする工程3と、同成
形体を非酸化性雰囲気中で焼成して焼結体とする工程4
とを含む製造方法で得られる。
The silicon carbide-based composite material of the present invention is formed into a compact by molding the powder obtained by the above-described procedure into a molded body, and the sintered body is sintered in a non-oxidizing atmosphere to form a sintered body. Step 4
And a production method comprising:

【0025】上記の工程4における焼成温度は、500
℃以上である方法、さらにはアルミニウムを主成分とす
る金属の融点以上である方法も本発明には含まれる。ま
た本発明の製造方法には、上記工程3の成形圧力が6t
on/cm2以上である方法、さらには同成形が温間、
特に100〜200℃で行われる方法も含まれる。
The firing temperature in the above step 4 is 500
The present invention also includes a method in which the temperature is higher than or equal to ° C. and a method in which the temperature is higher than the melting point of a metal containing aluminum as a main component. Further, in the production method of the present invention, the molding pressure in the above step 3 is 6 t.
on / cm 2 or more, and the molding is warm,
In particular, a method performed at 100 to 200 ° C is also included.

【0026】[0026]

【発明の実施の形態】本発明によって提供される炭化珪
素系複合材料の粉末ならびにこれを用いて得られる複合
材料は、第一成分がアルミニウムを主成分とする金属か
らなるもの(以下Al−SiC系複合材料または単にA
l−SiC系、Al系とも言う)である。本発明は、こ
の材料に着目し、放熱基板(ヒートシンク)、特に半導体
装置用の放熱基板の熱伝導性を向上させるためになされ
たものである。
BEST MODE FOR CARRYING OUT THE INVENTION The powder of a silicon carbide composite material provided by the present invention and the composite material obtained by using the same are those in which the first component is composed of a metal containing aluminum as a main component (hereinafter referred to as Al-SiC). Based composite material or simply A
1-SiC-based and Al-based). The present invention focuses on this material and has been made to improve the thermal conductivity of a heat dissipation substrate (heat sink), particularly a heat dissipation substrate for a semiconductor device.

【0027】本発明で提供される炭化珪素系複合材料の
粉末の平均粒径は、5〜100μmである。その個々の
粒子は、第一成分の複数の粒子が平均粒径5μm以下の
第二成分であるSiC粒子の表面を覆っている複合化さ
れた粒子である。また本発明の粉末全体のSiC粒子の
量は、10〜85重量%である。後述のようにこの粉末
は、両成分の混合物をメカニカルアロイング(Mech
anical Alloying、以下MAとも言う)
することによって得られる。メカニカルアロイングされ
複合化された粉末の平均粒径を上記の範囲内にする理由
は、下限未満では成形密度が上がらず、上限を越えると
アルミニウムの量が多くなり、メカニカルアロイング後
その容器に粉末が強固に付着して粉末の回収が困難とな
り、またその結果粉末の回収率が低下するからである。
好ましい平均粒径は、50〜100μmである。またそ
れに取り込まれた炭化珪素粒子の平均粒径を5μm以下
とするのは、それを越えると成形体の密度が十分上がら
ず、熱伝導率が低下するからである。好ましくは3μm
以下である。粉末中の炭化珪素の量を10〜85重量%
の範囲にするのは、下限未満では成形体を焼成する場
合、第一成分が溶けるとその形状保持が難しくなるから
である。また上限を越えると第一成分の融液量が少なく
なり焼成時の緻密化が十分進まないからである。
The average particle size of the powder of the silicon carbide composite material provided by the present invention is 5 to 100 μm. The individual particles are composite particles in which a plurality of particles of the first component cover the surface of the second component SiC particles having an average particle size of 5 μm or less. The amount of SiC particles in the whole powder of the present invention is 10 to 85% by weight. As described below, this powder is obtained by mechanically alloying a mixture of both components (Mech alloy).
(animal Alloying, hereinafter also referred to as MA)
It is obtained by doing. The reason why the average particle size of the mechanically alloyed and composited powder is within the above range is that the molding density does not increase below the lower limit, the amount of aluminum increases above the upper limit, and the mechanically alloyed container becomes This is because the powder adheres strongly and it becomes difficult to recover the powder, and as a result, the recovery rate of the powder decreases.
The preferred average particle size is 50 to 100 μm. The reason why the average particle diameter of the silicon carbide particles incorporated therein is 5 μm or less is that if the average particle diameter exceeds 5 μm, the density of the compact does not sufficiently increase and the thermal conductivity decreases. Preferably 3 μm
It is as follows. 10 to 85% by weight of silicon carbide in powder
If the first component is melted when the molded body is fired below the lower limit, it is difficult to maintain its shape. On the other hand, if it exceeds the upper limit, the amount of the melt of the first component decreases, and the densification during firing does not proceed sufficiently.

【0028】また本発明の炭化珪素系複合材料は、上記
の粉末を用いて得られ、その相対密度が90%以上、室
温での熱伝導率が220W/m・K以上の材料である。
相対密度が90%未満では熱伝導率が急激に低下する。
好ましくは94%以上である。なお相対密度とは、組成
より複合則によって計算された理論密度に対する実測密
度の割合である。
The silicon carbide-based composite material of the present invention is a material obtained by using the above powder, having a relative density of 90% or more and a thermal conductivity at room temperature of 220 W / m · K or more.
When the relative density is less than 90%, the thermal conductivity sharply decreases.
Preferably it is 94% or more. The relative density is the ratio of the measured density to the theoretical density calculated from the composition by the compound rule.

【0029】本発明の炭化珪素系複合材料の粉末は、第
一成分としてアルミニウムまたは銅を主成分とする金属
の粉末15〜90重量%および第二成分として平均粒径
が10〜200μmの炭化珪素粉末10〜85重量%を
準備する工程1と、これらの粉末を非酸化性雰囲気中で
第二成分の平均粒径が5μm以下になるまでメカニカル
アロイングする工程2とを含む方法で製造される。メカ
ニカルアロイング前の第二成分の平均粒径を上記の範囲
にするのは、下限未満では炭化珪素粒子表面の酸素量が
増加して、その酸素がアルミニウム粒子表面と反応して
アルミニウムの酸化物が生成し、後述するメカニカルア
ロイングによる両成分の間の化学的な密着が損なわれ
る。また上限を越えると炭化珪素が微細粒子まで粉砕さ
れず、両成分の複合化が不十分となる。その結果いずれ
の場合も緻密かつ優れた熱伝導性の材料が得られない。
The silicon carbide-based composite material powder of the present invention comprises 15 to 90% by weight of a metal powder mainly composed of aluminum or copper as a first component and silicon carbide having an average particle diameter of 10 to 200 μm as a second component. It is manufactured by a method including a step 1 of preparing powders 10 to 85% by weight and a step 2 of mechanically alloying these powders in a non-oxidizing atmosphere until the average particle size of the second component becomes 5 μm or less. . The reason why the average particle diameter of the second component before the mechanical alloying is set in the above range is that if the average particle diameter is less than the lower limit, the amount of oxygen on the surface of the silicon carbide particles increases, and the oxygen reacts with the surface of the aluminum particles to form an oxide of aluminum. Is generated, and the chemical adhesion between the two components due to mechanical alloying described later is impaired. If the upper limit is exceeded, the silicon carbide is not pulverized to fine particles, and the compounding of both components becomes insufficient. As a result, in any case, a dense and excellent heat conductive material cannot be obtained.

【0030】メカニカルアロイングの雰囲気は、第一成
分の酸化を避けるため、非酸化性雰囲気で行う。その際
通常のボールミル装置を用いてもよいが、粉砕エネルギ
ーの大きな遊星ボールミルを用いると短時間のMAが可
能となる。例えば両成分粉末と粉砕媒体のボールをこれ
らの装置のポットに充填し、ポットを自公転させて混合
粉砕する。ポットの回転加速度は10G以上とするのが
好ましい。10G未満では粉砕エネルギーが通常のボー
ルミルと大差が無く粉砕効率が低下し、粉砕に時間がか
かり過ぎることがある。なおこの回転加速度は、高いほ
ど粉砕効率は上がるが、本発明ではせいぜい150G程
度までである。それを越えると粉砕エネルギーがSiC
の粉砕に消費されず、むしろ同粒子に歪みを与え、その
結果その熱伝導性の低下を招くことがある。ポットの内
張りや粉砕媒体の材質は、耐摩耗性に優れたものであれ
ばよいが、例えば複合材料の主成分であるSiC系のも
のとするか、またはそれで被覆されたものを用いるのが
望ましい。
The mechanical alloying atmosphere is performed in a non-oxidizing atmosphere in order to avoid oxidation of the first component. In this case, a normal ball mill may be used, but if a planetary ball mill having a large crushing energy is used, MA can be performed in a short time. For example, both component powders and balls of a grinding medium are filled into pots of these apparatuses, and the pots are revolved around themselves and mixed and pulverized. It is preferable that the rotational acceleration of the pot be 10 G or more. If it is less than 10 G, the crushing energy is not so different from that of a normal ball mill, the crushing efficiency is reduced, and the crushing may take too much time. The higher the rotational acceleration is, the higher the crushing efficiency is, but in the present invention, it is at most about 150G. Beyond that, the grinding energy becomes SiC
Is not consumed in the milling of the particles, but rather distorts the particles, resulting in a decrease in thermal conductivity. The material of the pot lining and the crushing medium may be a material having excellent wear resistance, but it is preferable to use, for example, a SiC-based material which is a main component of the composite material, or a material coated therewith. .

【0031】本発明のメカニカルアロイングの過程で
は、当初平均粒径10〜200μmのSiC粒子は、そ
の進行とともに微粒化してゆく。一方当初の平均粒径が
通常数10〜数100μmの第一成分の粒子は、塑性変
形して微細化されたSiC粒子の周りを覆ってゆく。こ
れが繰り返されると、図1に模式的に示すように、微細
なSiC粒子の全表面を第一成分の多数の粒子が覆う二
次的に複合化された粒子が形成される。また第一成分粒
子の当初の表面には前述の如くその酸化物層が形成され
ているが、MAによってその層が破られ純粋な第一成分
金属からなり反応活性な表面が露呈する。一方破断され
たSiC粒子の表面も反応活性な面となる。これらの活
性面同志は、高いエネルギーの繰り返しの負荷で互いに
直接密着するとともに、それらの界面では固相反応が生
じ、化学的に結合した状態となる。
In the mechanical alloying process of the present invention, the SiC particles having an average particle diameter of 10 to 200 μm become finer as they proceed. On the other hand, the particles of the first component, whose initial average particle diameter is usually several tens to several hundreds of micrometers, cover around the SiC particles that have been plastically deformed and miniaturized. When this is repeated, as shown schematically in FIG. 1, secondary composite particles are formed in which the entire surface of the fine SiC particles is covered by a large number of particles of the first component. Although the oxide layer is formed on the initial surface of the first component particles as described above, the layer is broken by MA to expose a reactive surface composed of pure first component metal. On the other hand, the surface of the broken SiC particle also becomes a reactive surface. These active surfaces come into direct contact with each other under the repetitive load of high energy, and a solid-phase reaction occurs at their interface, resulting in a chemically bonded state.

【0032】微粒化された個々のSiC粒子のサイズ
は、小さいものでは1μm以下、さらには50nm程度
にまでになるが、MAはその平均粒径が5μm以下にな
るまで行う。5μmを越えると複合化された粒子の圧縮
性が下がり、圧力の上昇に伴う成形密度の上昇率が小さ
くなるので好ましくない。これは成形時の圧力によって
第一成分が塑性変形する際に、SiC粒子が小さいほど
その変形に対応して動き易いからである。このようにす
ると、複合化された粒子自体がそれに内蔵されるSiC
粒子に妨害されることなく、変形し易くなるので比較的
低い圧力でも成形は可能になる。その様子をMAを行っ
ていない単純混合の混合粉末と対比して、図2に模式的
に示す。同図の(a)がMAを行っていない粉末の場
合、(b)がMAを行った本発明の粉末の場合を示す。
従来の粉末では、成形時に第一成分が塑性変形すると、
その変形の及ぶ部分だけで粒子の密着が進み、変形に追
随しない大きなSiC粒子の全面を第一成分が覆うこと
ができず、第一成分が、それを取り込まない。その結果
成形後のSiC粒子表面のいくつかの部分に空隙が残
る。一方本発明の粉末ではSiC粒子が微粒化している
ため、それが第一成分の塑性変形の流れに応じて再配列
する。このため同じ圧力で成形しても図に示すように圧
縮性が顕著に異なる。両成分が広い界面で密着した本発
明の成形体を第一成分の融点以上の温度で加熱すると、
第一成分の融液とSiC粒子の表面が常圧下でも容易に
濡れ、それらの界面の空隙は大幅に少なくなる。その結
果同じ組成であっても熱伝導率は飛躍的に上昇する。
The size of each atomized SiC particle is as small as 1 μm or less, and further down to about 50 nm in the case of a small one. MA is performed until the average particle size becomes 5 μm or less. If it exceeds 5 μm, the compressibility of the composited particles is reduced, and the rate of increase in the molding density with an increase in pressure is undesirably reduced. This is because when the first component undergoes plastic deformation due to the pressure during molding, the smaller the SiC particles, the easier it is to move in response to the deformation. In this way, the composited particles themselves have SiC embedded therein.
Since it is easily deformed without being hindered by particles, molding can be performed even at a relatively low pressure. FIG. 2 schematically shows this state in comparison with a mixed powder of simple mixing without performing MA. (A) of the figure shows the case of the powder not subjected to MA, and (b) shows the case of the powder of the present invention subjected to MA.
With conventional powder, if the first component is plastically deformed during molding,
The adhesion of the particles progresses only at the portion where the deformation reaches, and the first component cannot cover the entire surface of the large SiC particle that does not follow the deformation, and the first component does not take in the same. As a result, voids remain in some parts of the surface of the SiC particles after molding. On the other hand, in the powder of the present invention, since the SiC particles are atomized, the SiC particles rearrange in accordance with the flow of the plastic deformation of the first component. For this reason, even if molded at the same pressure, the compressibility is significantly different as shown in the figure. Heating the molded article of the present invention in which both components adhere at a wide interface at a temperature equal to or higher than the melting point of the first component,
The surface of the melt of the first component and the surface of the SiC particles are easily wetted even under normal pressure, and voids at the interface between them are greatly reduced. As a result, even with the same composition, the thermal conductivity increases dramatically.

【0033】本発明の炭化珪素系複合材料は、以上の手
順で得られた粉末を成形し成形体とする工程3と、同成
形体を非酸化性雰囲気中で焼成して焼結体とする工程4
とを含む製造方法で得られる。成形方法は、限定されな
いが、乾式の粉末成形が生産効率上好ましい。成形時の
型は、耐摩耗性の材質であればよいが、例えば粉末と接
触する面は、SiC、ダイヤモンドおよびダイヤモンド
ライクカーボンのような硬質被覆を行うのが望ましい。
成形圧力は、通常は6ton/cm2以上が望ましい。
なお10ton/cm2以上の圧力をかけても成形密度
の上昇は期待出来ない。第一成分の塑性変形を促進し、
成形密度を上げるためには温間で行うのが望ましい。純
アルミニウムの場合、150℃程度が上限であるが、好
ましい成形温度は、100〜200℃である。なおアル
ミニウムにSiやMgのような従成分を少量含む合金粉
末を用いる場合には、その塑性変形を容易にするために
300℃程度まで昇温することもある。
The silicon carbide-based composite material of the present invention is obtained by molding the powder obtained by the above procedure into a molded body in step 3; and firing the molded body in a non-oxidizing atmosphere to form a sintered body. Step 4
And a production method comprising: The molding method is not limited, but dry powder molding is preferable in terms of production efficiency. The mold at the time of molding may be a wear-resistant material. For example, it is desirable that a surface that comes into contact with the powder be coated with a hard coating such as SiC, diamond, and diamond-like carbon.
The molding pressure is usually desirably 6 ton / cm 2 or more.
It should be noted that an increase in the molding density cannot be expected even when a pressure of 10 ton / cm 2 or more is applied. Promotes plastic deformation of the first component,
In order to increase the molding density, it is desirable to perform the warming. In the case of pure aluminum, the upper limit is about 150 ° C., but the preferred forming temperature is 100 to 200 ° C. When an alloy powder containing a small amount of a minor component such as Si or Mg in aluminum is used, the temperature may be raised to about 300 ° C. in order to facilitate its plastic deformation.

【0034】本発明の工程4の焼成温度は、通常第一成
分金属の融点以上が望ましい。ただし同金属の融点以下
の温度でも焼結は可能であり、比較的高い熱伝導性のも
のが得られる。その理由は、上記のように成形体中の複
合化された粒子中の両成分の界面が化学的に結合してい
るため熱伝導を妨げない程度の両成分間の接触が保たれ
るからである。この効果は、特にSiC粒子の量が50
重量%以下の組成域で顕著になる。ちなみに焼成温度の
下限は、500℃である。しかしながら通常は第一成分
金属の融点以上が望ましい。特に750℃までとするの
が望ましい。これはその温度を越えるとアルミニウムと
SiC粒子との界面で低熱伝導性の炭化アルミニウム
(Al4C3)が形成され、熱伝導率が低下し易いからで
ある。焼成の雰囲気は、例えば窒素のような非酸化性ガ
ス雰囲気であればよいが、真空中でも焼成は可能であ
る。また焼成は通常常圧下でよいが、例えばシンターH
IPのように加圧された条件下であればより一層緻密化
が進み易くなり、より一層優れた熱伝導性のものが得ら
れる。
The firing temperature in step 4 of the present invention is usually desirably equal to or higher than the melting point of the first component metal. However, sintering is possible even at a temperature lower than the melting point of the same metal, and a material having relatively high thermal conductivity can be obtained. The reason is that the interface between the two components in the composite particles in the molded article is chemically bonded as described above, so that the contact between the two components is maintained to the extent that heat conduction is not hindered. is there. This effect is particularly apparent when the amount of SiC particles is 50%.
It becomes remarkable in the composition range of not more than% by weight. Incidentally, the lower limit of the firing temperature is 500 ° C. However, the melting point of the first component metal is usually desirable. In particular, the temperature is desirably up to 750 ° C. This is because if the temperature is exceeded, aluminum carbide (Al 4 C 3 ) having low thermal conductivity is formed at the interface between aluminum and the SiC particles, and the thermal conductivity tends to decrease. The baking atmosphere may be a non-oxidizing gas atmosphere such as nitrogen, but baking is possible even in a vacuum. In addition, the sintering may be usually performed under normal pressure.
Under a pressurized condition such as IP, densification becomes easier to proceed, and more excellent thermal conductivity can be obtained.

【0035】アルミニウムを主成分とする第一成分の原
料は、市販のものを用いればよい。ただし合金元素を添
加した粉末を利用する場合を除き、複合材料の熱伝導率
を下げないためには、その主成分の純度の高いものを利
用するのが望ましい。例えば99%以上のものを用いる
のが望ましい。なお本発明で用いる第一成分の原料の使
用形態は、塊状・粉末状他のいかなる形態であってもよ
いが、通常は粉末状のものを用いる。原料粉末内に介在
する不純物種としては、合金元素を添加する場合を除
き、純金属を用いる場合には、第一成分の主成分金属中
に固溶し易い遷移金属元素、特に8a族元素を含む成分
を含む成分は、可能な限り少ないのが望ましい。なおさ
らに第一成分金属粉末の主成分の純度を高めるために
は、市販の粉末の中でも溶湯噴霧法や物理的または化学
的な処理法によって純度調整された粉末を準備する必要
がある。
As the raw material of the first component mainly composed of aluminum, a commercially available one may be used. However, in order not to lower the thermal conductivity of the composite material, it is preferable to use a high-purity main component of the composite material, except when using a powder to which an alloy element is added. For example, it is desirable to use 99% or more. The raw material of the first component used in the present invention may be in any form such as a lump, a powder, or the like, but usually a powder is used. Except for the case where an alloying element is added, when a pure metal is used as the impurity species interposed in the raw material powder, a transition metal element which is easily dissolved in the main component metal of the first component, particularly a Group 8a element, is used. It is desirable that the number of components including the components is as small as possible. Furthermore, in order to further increase the purity of the main component of the first component metal powder, it is necessary to prepare a powder whose purity has been adjusted by a melt spraying method or a physical or chemical treatment method among commercially available powders.

【0036】[0036]

【実施例】実施例1 第二成分として6H型の結晶粒子からなる表1の「Si
C原料」欄に記載の各種平均粒径のSiC粉末、第一成
分としていずれもその平均粒径が25μmの純アルミニ
ウム粉末とSiを5重量%含むアルミニウム合金粉末と
を準備した。表1に記載の配合量で各成分粉末を秤取し
MAを行った。SiC粉末の配合量は表1の「SiC原
料」欄に記載の重量部とし、第一成分の配合量はその残
部とした。第一成分粉末の種類は、表1の「第一成分」
欄に記載の粉末種とした。これらの粉末を直径3mmの
ステンレス鋼製のボールとともに遊星ボールミルのステ
ンレス鋼製のポット内に投入し、表1に記載の各試料毎
のポットの回転加速度および時間で混合粉砕し、複合化
された粉末とした。また試料1の粉末のみ表1に記載の
配合量の原料粉末を通常のボールミルで混合した。作製
した各粉末を樹脂に埋め込み、その断面を走査型電子顕
微鏡で3000倍に拡大して観察したところ、個々の粉
末は、微細化したSiC粒子の周りをアルミニウムを主
成分とする第一成分の複数の粒子で被覆された構造の粉
末であった。この粉末中に含まれるSiC粒子の平均粒
径と複合化粉末の平均粒径を測り、その結果を表1の
「複合化粉末」欄に示した。なお平均粒径は、いずれも
3000倍の矩形視野の写真を撮り、その2本の対角線
で切られた全ての粒子の長さを測ってそれらを算術平均
した値とした。
EXAMPLE 1 As a second component, "Si" in Table 1 was composed of 6H type crystal particles.
SiC powders having various average particle diameters described in the column of “C raw material”, pure aluminum powder having an average particle diameter of 25 μm, and aluminum alloy powder containing 5% by weight of Si were prepared as first components. Each component powder was weighed in the amount shown in Table 1 and subjected to MA. The compounding amount of the SiC powder was the parts by weight described in the “SiC raw material” column of Table 1, and the compounding amount of the first component was the rest. The type of the first component powder is the “first component” in Table 1.
The powder type described in the column was used. These powders were put into a stainless steel pot of a planetary ball mill together with a stainless steel ball having a diameter of 3 mm, and mixed and pulverized at the rotational acceleration and time of the pot for each sample shown in Table 1 to form a composite. Powder. Further, only the powder of the sample 1 was mixed with a raw material powder having the compounding amount shown in Table 1 by a usual ball mill. Each of the produced powders was embedded in a resin, and the cross section was observed at a magnification of 3000 times with a scanning electron microscope. As a result, each powder was found to have a first component mainly composed of aluminum around the micronized SiC particles. The powder had a structure coated with a plurality of particles. The average particle size of the SiC particles contained in the powder and the average particle size of the composite powder were measured, and the results are shown in the “Composite powder” column of Table 1. The average particle diameter was a value obtained by taking a photograph of a 3000-fold rectangular visual field, measuring the lengths of all particles cut by two diagonal lines, and arithmetically averaging them.

【0037】次ぎに各粉末を表1の「成形」欄に記載の
温度に昇温保持した金型内に入れ、同表に記載の圧力で
直径35mm、厚み10mmの形状に成形した。次いで
これらの各試料粉末を表1の「焼成」欄に記載の条件で
焼結した。また試料9の粉末は、別途同じ雰囲気ならび
に時間で、焼成温度のみ480℃および520℃とした
焼結体も作製した。試料7は、焼成後の形が崩れて製品
化は難しい組成であることが分かった。これらの焼結体
の相対密度、レーザーフラッシュ法で測った熱伝導率お
よび作動トランス式熱望張測定装置で計量した熱膨張係
数を表1の「焼結体」欄に示す。なお試料9の粉末を4
80℃および520℃で焼結した試料の相対密度は、前
者が96.1%、後者が97.5%であった。その結果
それぞれの熱伝導率は、前者が200W/m・K、後者
が220W/m・Kであった。
Next, each of the powders was placed in a mold maintained at a temperature shown in the column of "Molding" in Table 1 and formed into a shape having a diameter of 35 mm and a thickness of 10 mm under the pressure shown in the table. Next, each of these sample powders was sintered under the conditions described in the “calcination” column of Table 1. Further, as for the powder of Sample 9, a sintered body in which only the firing temperature was 480 ° C. and 520 ° C. was manufactured under the same atmosphere and time. Sample 7 was found to have a composition that was difficult to commercialize due to its collapsed shape after firing. The relative densities of these sintered bodies, the thermal conductivity measured by the laser flash method, and the coefficient of thermal expansion measured by a working transformer type thermal elongation measuring apparatus are shown in the column of "Sintered body" in Table 1. The powder of sample 9 was
The relative densities of the samples sintered at 80 ° C. and 520 ° C. were 96.1% for the former and 97.5% for the latter. As a result, the thermal conductivity was 200 W / m · K for the former and 220 W / m · K for the latter.

【0038】[0038]

【表1】 [Table 1]

【0039】以上の結果より以下のことが明らかとな
る。すなわち(1)MAを行いSiC粒子を5μm以下
に微細化し、その周りをアルミニウムを主成分とした第
一成分の粒子で覆った本発明の粉末は、単純な混合粉末
に比べ圧縮性に優れている。このため同じ圧力で成形す
ると、より高い成形密度のものが得られる。(2)この
粉末の成形体は、単純な混合粉末の成形体を焼結したも
のよりも高い熱伝導性の複合材料となる。500℃以上
の焼成温度、特に第一成分の融点以上の温度まで焼成温
度を上げると、220W/m・K以上の高い熱伝導率の
複合材料が容易に得られる。(3)SiC粒子の量が1
0重量%未満の粉末および85重量%を越える複合粉末
を用い第一成分の融点以上で焼成すると、前者はその形
状が保持できなくなり、後者は相対密度が90%未満と
なり、熱伝導率は低下する。
The following becomes clear from the above results. That is, (1) the powder of the present invention in which the SiC particles are refined to 5 μm or less by performing MA and the periphery thereof is covered with particles of the first component containing aluminum as a main component is superior in compressibility as compared with a simple mixed powder. I have. Therefore, when molding is performed under the same pressure, a molded article having a higher molding density can be obtained. (2) The compact of this powder becomes a composite material having a higher thermal conductivity than that obtained by sintering a compact of a simple mixed powder. When the firing temperature is increased to 500 ° C. or higher, particularly to the temperature equal to or higher than the melting point of the first component, a composite material having a high thermal conductivity of 220 W / m · K or higher can be easily obtained. (3) The amount of SiC particles is 1
When sintering at a temperature higher than the melting point of the first component using less than 0% by weight of powder and more than 85% by weight of composite powder, the former cannot maintain its shape, and the latter has a relative density of less than 90%, and the thermal conductivity decreases. I do.

【0040】実施例2 実施例1の試料3、4、10、14、18と同じ製法で
得た焼結体50個ずつを長さ200mm、幅200m
m、厚み3mmの基材に仕上げ加工した。これを図3に
模式的に示すようなパワーモジュールに放熱基板として
実装して、各実装段階も含めて温度サイクル試験を行っ
た。図3において、1は本発明の上記複合材料からなる
第二の放熱基板、2は同基板上に配置され、その上面に
(図示しないが)銅回路が形成されたセラミックスからな
る電気絶縁性の第一の基板、3はSi半導体素子、4は
第二の放熱基板の下に配置された放熱構造体である。な
おこのジャッケットは、本実施例では水冷ジャケットで
あるが、他に空冷のフィン等もある。なお同図には半導
体素子周辺の配線等については省略してある。本実施例
では、Si半導体素子を第一のセラミックス製基板を介
して6個搭載したモジュールとした。
Example 2 Fifty sintered bodies obtained by the same manufacturing method as Samples 3, 4, 10, 14, and 18 of Example 1 were each 200 mm long and 200 m wide.
m and a thickness of 3 mm. This was mounted on a power module as schematically shown in FIG. 3 as a heat radiating substrate, and a temperature cycle test was performed including each mounting step. In FIG. 3, reference numeral 1 denotes a second heat radiation substrate made of the above-described composite material of the present invention, and 2 denotes a second heat radiation substrate disposed on the same substrate.
An electric insulating first substrate (not shown) made of ceramics on which a copper circuit is formed, 3 is a Si semiconductor device, and 4 is a heat dissipation structure disposed below the second heat dissipation substrate. The jacket is a water-cooled jacket in the present embodiment, but may also include air-cooled fins. It should be noted that wiring and the like around the semiconductor element are omitted in FIG. In the present embodiment, a module was used in which six Si semiconductor elements were mounted via the first ceramic substrate.

【0041】実装に先立ち第二の基板に直接第一の基板
を半田付けできないため、第二の基板の主面に予め平均
厚み5μmの無電解ニッケルメッキ層と平均厚み3μm
の電解ニッケルメッキ層を形成した。この内各4個の試
片は、ニッケルメッキ上に直径5mmの半球状のAg−
Sn系半田によって直径1mmの銅線をメッキ面に垂直
な方向に取り付けた。この試片の基板本体を治具に固定
して銅線を掴みメッキ面に垂直な方向に引っ張り、基板
へのメッキ層の密着強度を確認した。その結果いずれの
基板のメッキ層も1kg/mm2以上の引っ張り力でも
剥がれなかった。またメッキ層が形成された別の試片の
内から10個を抜き取って、−60℃で30分保持、1
50℃で30分保持の昇降温を1000サイクル繰り返
すヒートサイクル試験を実施し、試験後上記と同様の密
着強度を確認したところ、いずれの試片もメッキの密着
性で上記レベルを満足する結果が得られた。以上の結果
より本発明の複合材料からなる基板へのメッキの密着性
は、実用上問題の無いレベルであることが判明した。
Since the first substrate cannot be directly soldered to the second substrate prior to mounting, an electroless nickel plating layer having an average thickness of 5 μm and an average thickness of 3 μm
An electrolytic nickel plating layer was formed. Each of the four specimens was a 5 mm diameter hemispherical Ag-
A copper wire having a diameter of 1 mm was attached in a direction perpendicular to the plating surface by Sn-based solder. The substrate body of this specimen was fixed to a jig, a copper wire was grasped and pulled in a direction perpendicular to the plating surface, and the adhesion strength of the plating layer to the substrate was confirmed. As a result, none of the plating layers of any of the substrates was peeled off even with a tensile force of 1 kg / mm 2 or more. Also, 10 samples were taken out of another sample on which the plating layer was formed, and held at −60 ° C. for 30 minutes.
A heat cycle test was performed by repeating 1000 cycles of raising and lowering the temperature for 30 minutes at 50 ° C., and after the test, the same adhesion strength as above was confirmed. Obtained. From the above results, it was found that the adhesion of the plating to the substrate made of the composite material of the present invention was at a level having no practical problem.

【0042】次に第二の基板上に搭載するセラミックス
製の第一の基板として、熱伝導率が150W/m・K、
熱膨張係数が4.5×10-6/℃、3点曲げ強度450
MPaの窒化アルミニウムセラミックス製の基板Aおよ
び熱伝導率が120W/m・K、熱膨張係数が3.7×
10-6/℃、3点曲げ強度1300MPaの窒化珪素セ
ラミックス製の基板Bの二種の銅回路を形成した第一の
基板を、それぞれ18個ずつ準備した。これらの基板の
形状は、いずれも長さ90mm、幅60mm、厚み1m
mとした。これらの基板を第二の基板の200mm角の
主面上に2行3列で等間隔に配置し、同基板のニッケル
メッキ層を形成した面上にAg−Sn系半田によって固
定した。次にこのアッセンブリーの第二の基板の裏面側
と水冷ジャケットとを、その接触面にシリコンオイルコ
ンパウンドを塗布介在させてボルト閉め固定した。なお
この場合の第一の基板の取り付け穴は、予め素材段階で
その四隅に開けておいた下穴部に炭酸ガスレーザーを照
射して、それを直径3mmまで拡げる方法によって形成
した。この加工は他のセラミックス材やCu−W、Cu
−Moを対象とした場合に比べ、高精度かつ高速で行う
ことができた。この傾向は特に熱伝導率が高くなればな
るほど顕著であった。
Next, as a first ceramic substrate mounted on the second substrate, a thermal conductivity of 150 W / m · K,
Thermal expansion coefficient 4.5 × 10 -6 / ° C, three-point bending strength 450
A substrate made of aluminum nitride ceramics of MPa, thermal conductivity of 120 W / m · K, thermal expansion coefficient of 3.7 ×
10 -6 / ° C., first a substrate formed with two copper circuits of silicon nitride ceramic substrate B of 3-point bending strength 1300 MPa, were prepared by 18 each. Each of these substrates has a length of 90 mm, a width of 60 mm, and a thickness of 1 m.
m. These substrates were arranged at equal intervals in two rows and three columns on a 200 mm square main surface of the second substrate, and were fixed on the surface of the same substrate on which the nickel plating layer was formed by Ag-Sn solder. Next, the back surface of the second substrate of the assembly and the water-cooled jacket were fixed with bolts closed by applying a silicone oil compound to the contact surface thereof. In this case, the mounting holes of the first substrate were formed by irradiating a carbon dioxide gas laser to the prepared holes previously formed in the four corners at the material stage, and expanding the holes to a diameter of 3 mm. This processing is performed using other ceramic materials, Cu-W, Cu
-Higher accuracy and higher speed than in the case of Mo. This tendency was particularly remarkable as the thermal conductivity increased.

【0043】これらの各試片の中から第一の基板がAと
Bの物を各15個ずつ選び、上記と同じ単サイクル条件
で2000サイクルのヒートサイクル試験を行い、その
500サイクル毎のモジュールの出力の変化を確認し
た。その結果、全てのモジュールが、実用上問題が無い
とされる1000サイクルまで、さらに2000サイク
ルまで試験を続行したが、その出力の低下は観測されな
かった。以上の結果より、本発明の炭化珪素系複合材料
からなる第一の基板を用いたパワーモジュールは、実用
上問題の無いレベルのものとなることが分かる。
From each of these test pieces, 15 first substrates A and B were selected and subjected to a heat cycle test of 2,000 cycles under the same single cycle conditions as described above. The change in output was confirmed. As a result, all the modules continued the test up to 1000 cycles, which is considered to be no problem in practical use, and further up to 2000 cycles, but no decrease in output was observed. From the above results, it can be seen that the power module using the first substrate made of the silicon carbide-based composite material of the present invention has a practically acceptable level.

【0044】なお本発明の材料をこの種のモジュールに
比べ低出力・低熱(サイクル)負荷の高容量のパーソナル
コンピューター等の半導体素子搭載装置に放熱基板とし
て実装・評価も行ったが、その信頼性・実用性能上何ら
問題は無かった。
The material of the present invention was mounted and evaluated as a heat radiation board on a semiconductor device mounting device such as a personal computer having a low output and a low heat (cycle) load and a high capacity compared to this type of module. -There was no problem in practical performance.

【0045】[0045]

【発明の効果】以上詳述したように、本発明によれば炭
化珪素(SiC)粒子を主成分とする粉末と、アルミニウ
ムを主成分とする粉末とを、メカニカルアロイングし
て、5μm以下の平均粒径までSiC粒子を微細化する
とともに、それら粒子の周りが第一成分の複数の粒子が
覆った構造の複合粉末を形成することにより、単純に混
合した同じ組成の従来の粉末よりより高い圧縮性の粉末
が得られる。この粉末を成形し焼結することによって、
相対密度が90%以上、熱伝導率が220W/m・K以
上の優れた半導体装置に有用な優れた炭化珪素系複合材
料が得られる。したがって、本発明の炭化珪素複合材料
は、半導体素子を搭載する放熱基板、特に高出力のパワ
ーモジュール用の高信頼性の放熱基板として有用であ
る。
As described above in detail, according to the present invention, a powder mainly containing silicon carbide (SiC) particles and a powder mainly containing aluminum are subjected to mechanical alloying to form a powder having a particle size of 5 μm or less. By making the SiC particles finer to an average particle size and forming a composite powder around the particles covered by a plurality of particles of the first component, higher than conventional powders of the same composition simply mixed A compressible powder is obtained. By molding and sintering this powder,
An excellent silicon carbide composite material useful for an excellent semiconductor device having a relative density of 90% or more and a thermal conductivity of 220 W / m · K or more can be obtained. Therefore, the silicon carbide composite material of the present invention is useful as a heat-dissipating substrate on which a semiconductor element is mounted, particularly a highly reliable heat-dissipating substrate for a high-output power module.

【図面の簡単な説明】[Brief description of the drawings]

【図1】本発明粉末のメカニカルアロイング過程を模式
的に説明する図である。
FIG. 1 is a diagram schematically illustrating a mechanical alloying process of the powder of the present invention.

【図2】本発明粉末と従来の単純混合された粉末の成形
過程を比較し、両者の相違点を模式的に説明する図であ
る。
FIG. 2 is a diagram comparing molding processes of a powder of the present invention and a conventional powder that is simply mixed, and schematically explaining the differences between the two.

【図3】本発明の材料を基板に用いた半導体装置(パワ
ーモジュール)を模式的に示す図である。
FIG. 3 is a diagram schematically showing a semiconductor device (power module) using a material of the present invention for a substrate.

【符号の説明】[Explanation of symbols]

1、炭化珪素系複合材料からなる第一基板 2、第二基板 3、半導体素子 4、放熱構造体 1. First substrate 2, second substrate 3, semiconductor element 4, heat dissipation structure made of silicon carbide composite material

───────────────────────────────────────────────────── フロントページの続き (51)Int.Cl.7 識別記号 FI テーマコート゛(参考) C22C 32/00 C22C 32/00 Q H01L 23/373 H01L 23/36 M ──────────────────────────────────────────────────の Continued on the front page (51) Int.Cl. 7 Identification symbol FI Theme coat ゛ (Reference) C22C 32/00 C22C 32/00 Q H01L 23/373 H01L 23/36 M

Claims (12)

【特許請求の範囲】[Claims] 【請求項1】 アルミニウムを主成分とする金属を第一
成分とし、炭化珪素を主成分とする粒子を第二成分とす
る炭化珪素系複合材料の粉末であって、その平均粒径は
5〜100μmであり、その個々の粒子は、平均粒径5
μm以下の第二成分の粒子表面を第一成分の複数の粒子
が覆っており、該粉末全体の炭化珪素の量が10〜85
重量%である炭化珪素系複合材料の粉末。
A powder of a silicon carbide-based composite material containing a metal containing aluminum as a main component as a first component and particles containing silicon carbide as a main component as a second component. 100 μm, the individual particles having an average particle size of 5
A plurality of particles of the first component cover the particle surface of the second component having a particle size of μm or less, and the amount of silicon carbide in the entire powder is 10 to 85.
A powder of a silicon carbide-based composite material which is in weight%.
【請求項2】 前記炭化珪素系複合材料の粉末を用いて
得られ、その相対密度が90%以上、室温での熱伝導率
が220W/m・K以上の炭化珪素系複合材料。
2. A silicon carbide-based composite material obtained by using the powder of the silicon carbide-based composite material and having a relative density of 90% or more and a thermal conductivity at room temperature of 220 W / m · K or more.
【請求項3】 請求項2に記載の炭化珪素系複合材料を
用いた半導体装置。
3. A semiconductor device using the silicon carbide composite material according to claim 2.
【請求項4】 アルミニウムを主成分とする金属を第一
成分とし、炭化珪素を主成分とする粒子を第二成分とす
る炭化珪素系複合材料の粉末の製造方法であって、第一
成分としてアルミニウムを主成分とする金属の粉末15
〜90重量%および第二成分として平均粒径が10〜2
00μmの炭化珪素粉末10〜85重量%を準備する工
程1と、これらの粉末を非酸化性雰囲気中で第二成分の
平均粒径が5μm以下になるまでメカニカルアロイング
する工程2とを含む炭化珪素系複合材料の粉末の製造方
法。
4. A method for producing a powder of a silicon carbide-based composite material comprising a metal having aluminum as a main component as a first component and particles having silicon carbide as a main component as a second component. Powder 15 of a metal mainly composed of aluminum
~ 90% by weight and an average particle size of 10-2 as a second component
A step 1 of preparing 10 to 85% by weight of silicon carbide powder of 00 μm and a step 2 of mechanically alloying these powders in a non-oxidizing atmosphere until the average particle size of the second component becomes 5 μm or less. A method for producing a powder of a silicon-based composite material.
【請求項5】 前記工程2は、10G以上の加速度でメ
カニカルアロイングする請求項4に記載の炭化珪素系複
合材料の粉末の製造方法。
5. The method for producing a powder of a silicon carbide composite material according to claim 4, wherein in the step 2, mechanical alloying is performed at an acceleration of 10 G or more.
【請求項6】 アルミニウムを主成分とする金属を第一
成分とし、炭化珪素を主成分とする粒子を第二成分とす
る炭化珪素系複合材料の製造方法であって、第一成分と
してアルミニウムを主成分とする金属の粉末15〜90
重量%および第二成分として平均粒径が10〜200μ
mの炭化珪素粉末10〜85重量%を準備する工程1
と、これらの粉末を非酸化性雰囲気中で第二成分の平均
粒径が5μm以下になるまでメカニカルアロイングして
炭化珪素系複合材料の粉末とする工程2と、該粉末を成
形し成形体とする工程3と、該成形体を非酸化性雰囲気
中で焼成して焼結体とする工程4とを含む炭化珪素系複
合材料の製造方法。
6. A method for producing a silicon carbide composite material comprising a metal having aluminum as a main component as a first component and particles having silicon carbide as a main component as a second component, wherein aluminum is used as the first component. Metal powder 15 to 90 as main component
% By weight and an average particle size of 10 to 200 μm as the second component
Step 1 of preparing 10 to 85% by weight of silicon carbide powder
And 2) mechanically alloying these powders in a non-oxidizing atmosphere until the average particle size of the second component becomes 5 μm or less to obtain a powder of a silicon carbide composite material. And a step 4 of firing the compact in a non-oxidizing atmosphere to form a sintered body.
【請求項7】 前記工程2は、10G以上の加速度でメ
カニカルアロイングする請求項6に記載の炭化珪素系複
合材料の製造方法。
7. The method of manufacturing a silicon carbide composite material according to claim 6, wherein in the step 2, mechanical alloying is performed at an acceleration of 10 G or more.
【請求項8】 前記工程4は、焼成温度が500℃以上
である請求項6または7に記載の炭化珪素系複合材料の
製造方法。
8. The method for producing a silicon carbide composite material according to claim 6, wherein in step 4, the firing temperature is 500 ° C. or higher.
【請求項9】 前記焼成温度は、第一成分の融点以上で
ある請求項6ないし8のいずれかに記載の炭化珪素系複
合材料の製造方法。
9. The method for producing a silicon carbide-based composite material according to claim 6, wherein the firing temperature is equal to or higher than the melting point of the first component.
【請求項10】 前記工程3は、6ton/cm2以上
の圧力で成形する請求項6ないし9のいずれかに記載の
炭化珪素系複合材料の製造方法。
10. The method for producing a silicon carbide-based composite material according to claim 6, wherein the step 3 is performed under a pressure of 6 ton / cm 2 or more.
【請求項11】 前記工程3は、温間で成形する請求項
6ないし9のいずれかに記載の炭化珪素系複合材料の製
造方法。
11. The method for producing a silicon carbide-based composite material according to claim 6, wherein the step 3 is performed during warm forming.
【請求項12】 前記温間で成形する温度が、100〜
200℃である請求項11に記載の炭化珪素系複合材料
の製造方法。
12. The molding temperature in the warm state is 100 to 100.
The method for producing a silicon carbide-based composite material according to claim 11, wherein the temperature is 200 ° C.
JP11107395A 1999-04-15 1999-04-15 Silicon carbide-based composite material, powder thereof, and production method thereof Pending JP2000297301A (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
JP11107395A JP2000297301A (en) 1999-04-15 1999-04-15 Silicon carbide-based composite material, powder thereof, and production method thereof

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
JP11107395A JP2000297301A (en) 1999-04-15 1999-04-15 Silicon carbide-based composite material, powder thereof, and production method thereof

Publications (1)

Publication Number Publication Date
JP2000297301A true JP2000297301A (en) 2000-10-24

Family

ID=14458064

Family Applications (1)

Application Number Title Priority Date Filing Date
JP11107395A Pending JP2000297301A (en) 1999-04-15 1999-04-15 Silicon carbide-based composite material, powder thereof, and production method thereof

Country Status (1)

Country Link
JP (1) JP2000297301A (en)

Cited By (10)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2002338365A (en) * 2001-05-14 2002-11-27 Sumitomo Electric Ind Ltd Aluminum nitride based composite powder and method for producing the same
KR100413547B1 (en) * 2001-05-29 2003-12-31 한국기계연구원 Aluminum matrix composite materials with high thermal conductivity and low thermal expansivity for electronic packaging, and manufacturing method therefor
WO2004008530A1 (en) * 2002-07-17 2004-01-22 Sumitomo Electric Industries, Ltd. Member for semiconductor device
US8803183B2 (en) 2010-10-13 2014-08-12 Ho Cheng Industrial Co., Ltd. LED heat-conducting substrate and its thermal module
US10059631B2 (en) 2016-11-15 2018-08-28 Industrial Technology Research Institute Micropowder and method for manufacturing the same
JP2021084363A (en) * 2019-11-28 2021-06-03 キヤノン株式会社 Method for producing article and powder
CN113264775A (en) * 2020-01-29 2021-08-17 日本碍子株式会社 Dense composite material, method for producing same, joined body, and member for semiconductor manufacturing apparatus
JP2021523011A (en) * 2018-05-08 2021-09-02 マテリオン コーポレイション How to Make Metal Matrix Composite Strip Products
JP2021523012A (en) * 2018-05-08 2021-09-02 マテリオン コーポレイション How to heat strip products
CN114068333A (en) * 2020-07-30 2022-02-18 比亚迪半导体股份有限公司 Heat dissipation plate and preparation method thereof

Cited By (16)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
JP2002338365A (en) * 2001-05-14 2002-11-27 Sumitomo Electric Ind Ltd Aluminum nitride based composite powder and method for producing the same
KR100413547B1 (en) * 2001-05-29 2003-12-31 한국기계연구원 Aluminum matrix composite materials with high thermal conductivity and low thermal expansivity for electronic packaging, and manufacturing method therefor
WO2004008530A1 (en) * 2002-07-17 2004-01-22 Sumitomo Electric Industries, Ltd. Member for semiconductor device
JP2004104074A (en) * 2002-07-17 2004-04-02 Sumitomo Electric Ind Ltd Semiconductor device components
CN100343986C (en) * 2002-07-17 2007-10-17 住友电气工业株式会社 Member for semiconductor device
US8803183B2 (en) 2010-10-13 2014-08-12 Ho Cheng Industrial Co., Ltd. LED heat-conducting substrate and its thermal module
US10059631B2 (en) 2016-11-15 2018-08-28 Industrial Technology Research Institute Micropowder and method for manufacturing the same
US10214454B2 (en) 2016-11-15 2019-02-26 Industrial Technology Research Institute Structure of micropowder
JP2021523012A (en) * 2018-05-08 2021-09-02 マテリオン コーポレイション How to heat strip products
JP7527973B2 (en) 2018-05-08 2024-08-05 マテリオン コーポレイション Method for heating strip products
JP2021523011A (en) * 2018-05-08 2021-09-02 マテリオン コーポレイション How to Make Metal Matrix Composite Strip Products
JP2021084363A (en) * 2019-11-28 2021-06-03 キヤノン株式会社 Method for producing article and powder
JP7406900B2 (en) 2019-11-28 2023-12-28 キヤノン株式会社 Article manufacturing method and powder
CN113264775B (en) * 2020-01-29 2023-07-04 日本碍子株式会社 Compact composite material, method for producing the same, bonded body, and member for semiconductor manufacturing device
CN113264775A (en) * 2020-01-29 2021-08-17 日本碍子株式会社 Dense composite material, method for producing same, joined body, and member for semiconductor manufacturing apparatus
CN114068333A (en) * 2020-07-30 2022-02-18 比亚迪半导体股份有限公司 Heat dissipation plate and preparation method thereof

Similar Documents

Publication Publication Date Title
US6114048A (en) Functionally graded metal substrates and process for making same
EP0987231B1 (en) Silicon carbide based composite material and manufacturing method thereof
JP4360061B2 (en) Semiconductor device member and semiconductor device using the same
JP2000303126A (en) Diamond-aluminum composite material and method for producing the same
US6123895A (en) Aluminum base member for semiconductor device containing a nitrogen rich surface and method for producing the same
JPH09157773A (en) Low thermal expansion / high thermal conductivity aluminum composite material and method for producing the same
JPWO2000076940A1 (en) Composite material and semiconductor device using the same
JP2000336438A (en) Metal-ceramic composite material and method for producing the same
JP3408298B2 (en) High thermal conductive silicon nitride metallized substrate, method of manufacturing the same, and silicon nitride module
JP2001335859A (en) Aluminum-silicon carbide based composite material and method for producing the same
JP4314675B2 (en) Silicon carbide powder, composite material using the same, and manufacturing method thereof
JP3449683B2 (en) Ceramic circuit board and method of manufacturing the same
JP2021116218A (en) Dense composite material, method for producing the same, joined body, and member for semiconductor manufacturing device
JP4305986B2 (en) Method for producing silicon carbide composite material
JP4228444B2 (en) Silicon carbide based composite material and method for producing the same
JP4253932B2 (en) Method for producing silicon carbide composite material
JP4461513B2 (en) Aluminum-silicon carbide based composite material and method for producing the same
JP2677748B2 (en) Ceramics copper circuit board
JP4275892B2 (en) Manufacturing method of semiconductor element mounting substrate material
JP4269853B2 (en) Composite material for substrate for mounting semiconductor element and method for manufacturing the same
JP3948797B2 (en) Method for producing silicon carbide composite
JPH11116361A (en) Silicon carbide-based composite and heat radiating part using the same
JP2002121639A (en) Heat dissipation board and high power high frequency transistor package using it
JP2000311972A (en) Semiconductor device
JP2815656B2 (en) High-strength heat-radiating structural member for packaged semiconductor devices